MEMBENTUK PRIBADI MULIA MELALUI PENDIDIKAN NILAI: Studi Di SD Muhammadiyah Bodon Yogyakarta - Sudrajat sudrajat (Informasi, 2011)
Spread corruption, collution and nepotism and increase of drugs, criminality etc. on the other hand was one of moral collapse in our nation. This phenomena was standpoint from morality mozaik from our generation and must be solved to make our nations better. The eduation is one of the most useful to revamp our generation, and values education must be implemented in schools. This research used of qualitative method to thoroughly find fact and phenomena which the researcher himself as the instrument. The researcher used in-depth interview, participatory observation, and documentation to collect the data. The validity data is acquired by triangulation, the longer observation, negative case analysis, and references to check and recheck. The researcher used interactive data analysis method by Miles and Huberman to analyze the data which includes: data reduction, data display and conclusion. The result shows that the headmaster, teacher, and staff of Muhammadiyah Bodon of Elementary School have significant role in the implementation of values education. As a manager, the headmaster planed, organized and evaluated the program. The teachers took the role of values educator, model to values teaching, supervisor and evaluator to values education program. The values education programs in Muhammadiyah Bodon Elementary School was implemented by comprehensive models that was integrated in learning, extracurricular, and particular events. The values developed in that school were the values of religion, clean and beauty, discipline, politeness, and honesty. The impacts of values education on the performance of students of Muhammadiyah Bodon Elementary School was significant. This can be seen from their achievements in school cleaning competitions, religion competitions, “batik” contest, Javanese speech contest etc. The factors that encouraged the implementations of values education were: good capability of human resources, school facilities, some programs which were in line with values education, and the active role of the school elements. The factors that discouraged values education program were: few of teachers who did not appreciate to values education programs, parents who did not care with affective education to their children, and the environment did not care with the implementation of values education in Muhammadiyah Bodon Elementary School.   Key words: Values, education, Muhammadiyah